2017
DOI: 10.3945/jn.116.244426
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Absorption from Milk Is Affected by Dilution but Not by Thermal Processing, and Milk Enhances Absorption of Zinc from High-Phytate Rice in Young Dutch Women

Abstract: Milk has been suggested to increase zinc absorption. The effect of processing and the ability of milk to enhance zinc absorption from other foods has not been measured directly in humans. We aimed to assess zinc absorption from ) milk undergoing various processing and preparatory steps and) from intrinsically labeled high-phytate rice consumed with milk or water. Two randomized crossover studies were conducted in healthy young women [age:18-25 y; body mass index (in kg/m): 20-25]: ) a milk study ( = 19) compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Moreover, Sandstrom et al [50] reported a significantly (p < 0.05) higher zinc absorption from bovine milk compared to a soy formula (28 vs. 14%) that was high in phytic acid (200 mg/L), which is agrees with the understanding that phytates are powerful inhibitors of zinc uptake [15]. Talsma et al [52], using a dual stable isotope technique, found lower zinc absorption from bovine milk compared to water (25.5 vs. 72.3%). This is probably because water does not contain inhibitory factors that reduce zinc absorption [53].…”
Section: Zinc Absorption From Dairy Productssupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, Sandstrom et al [50] reported a significantly (p < 0.05) higher zinc absorption from bovine milk compared to a soy formula (28 vs. 14%) that was high in phytic acid (200 mg/L), which is agrees with the understanding that phytates are powerful inhibitors of zinc uptake [15]. Talsma et al [52], using a dual stable isotope technique, found lower zinc absorption from bovine milk compared to water (25.5 vs. 72.3%). This is probably because water does not contain inhibitory factors that reduce zinc absorption [53].…”
Section: Zinc Absorption From Dairy Productssupporting
confidence: 58%
“…In these studies, zinc absorption was determined in vivo by isotope techniques. Talsma et al [52] examined the effect of milk on zinc absorption from rice in 18 young and healthy women using a dual stable isotopes technique and found a significant (p < 0.05) increase (by 62%) in zinc absorption from rice when 90 g of high-phytate rice was consumed together with 600 mL of UHT-treated whole milk, compared to when the same amount of rice was consumed with water. Rosado et al [55] studied zinc absorption in 48 healthy Mexican women, using a stable double isotope technique, and observed that the addition of 250 mL of UHT low-fat milk or 150 g of flavored yogurt to the plant-based test meal, consisting of 120 g of corn tortillas and 200 g of cooked black beans, significantly (p < 0.05) increased zinc absorption by approximately 50% for milk and 68% yoghurt.…”
Section: Zinc Absorption From Meals Containing Dairy Productsmentioning
confidence: 99%
“…Low dietary intake of absorbable Zn is the primary cause of Zn deficiency. In a study by Talsma et al (2017), consuming a combination of milk and phytate-rich rice increased the total amount of absorbable Zn from rice, suggesting that Zn-rich dairy products can potentially increase dietary absorbable Zn concentration. Ianni et al (2019) found that feeding dairy animals with Zn was a promising method to increase Zn content in dairy products.…”
mentioning
confidence: 99%
“…Mechanism of alterations of those three elements due to acrylamide exposure and intermittent fasting are not clear but in similar studies (22), acrylamide was shown to exert prominent effect on some other elements (cobalt, vanadium, magnesium, selenium). Absorption of elements taken with diet is closely related with diet content and substances such as phytates directly affect absorption (25). There are no detailed data concerning effects of acrylamide on those food ingredients.…”
Section: Discussionmentioning
confidence: 99%